The Stamp : newsletter of the gay movement of Bergen. (Bergen : HBB, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : onregelmatig
Redactie : PO Box 4260, 5013 Bergen-Nygardstangen [Noorwegen]
Engels
Periodiek